STATUS HUKUM TRANSAKSI GO-PAY PERSPEKTIF ISLAM - Aris Badaruddin Thoha (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
E-money (electronic money) is present as an alternative non-cash payment instrument, especially for micro payments to retail. The emergence of e-money in Indonesia was motivated by the Bank Indonesia Regulation Number 11/12 / PBI / 2009 as one of the supporters of the Bank Indonesia agenda to create a less cash society in Indonesia. E-money itself aims to make it easier for humans to carry out all kinds of economic transactions in their lives, especially for micro payments. One electronic money that has obtained a license (permit) from Bank Indonesia is the Go-Pay owned by the company PT Dompet Karya Anak Bangsa. The Bank Indonesia permit was submitted on September 29, 2014. Go-Pay is the result of the development of payment technology, namely electronic money virtual where Go-Pay is not in the form of card pay but in the form of a Go-Jek account. Go-Pay is believed to be a form of payment that makes it easier for the customer to pay for various transactions in the Go-Jek application, because with this mechanism the customer does not need to provide cash and pay in cash. Even customers can easily refill balance or top-up balance to a Go-Pay account. One of the discussions in the community regarding transactions using Go-Pay is a discount. Some scholars say that the discount is an additional benefit called usury, while others say the added benefit of discounting is not a form of usury.Based on the background that has been stated, the formulation of the problem in this study is how the legal status of Go-Pay transactions in the Islamic perspective is associated with the existence of additional benefits? To answer this problem, library research with a normative qualitative approach is conducted and processing techniques and data analysis use qualitative methods. The results of this study are that the contract that occurs between the issuer and the Go-Pay user when the user performs top-up is the contract wadi'ah (deposit) or qardh contract (accounts payable). The discount in transactions using Go-Pay does not include usury, because the discount is not given by Go-Pay as a publisher but by Go-Jek as the owner of the application where Go-Pay and Go-Jek are two different entities.